Acidente do trabalho: responsabilidade civil do empregador e culpa exclusiva do empregado - Polizel, Rosana Boscariol Bataini (2014)
The present study aims to analyze accidents in relations between employee and employer, i.e. studying workplace accidents in latu sensu sense. Thus, the purpose is to demonstrate through the chapters the central idea of the issue, starting from the research of all aspects that involve it. The first chapter discusses the concept of occupational accidents, since its historical, the typicality of the accident, the occupational illness to the joint cause, the indirect causation and the accident path. The second chapter highlights the liability in a broad sense, encompassing contractual liability, extra-contractual, subjective and objective. The third chapter goes deeply to the civil liability of employers in workplace accidents in its various aspects, including equipment damages, moral and their respective compensation. The fourth chapter brings the exclusive fault of the employee, which is necessary to be very accurate, so that it can be exclusive responsibility of the employer. The fifth and final chapter refers to the infamous prescription in labor accidents that still generates a lot of discussion regarding the subject matter described herein